Spotlight on Practice - Martin, Heather (Operating Room Nurses Association of Canada Journal, 2025)
Did you know ... Each new edition of the ORNAC Guidelines takes nearly two years to produce! Almost immediately after the publication of one edition, we begin work on the next by recruiting volunteer ORNAC members to form a new committee. The first step is to define the scope of the new edition, identify the content to be revised and additional topics to consider, and editorial changes to be applied throughout the document.